Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Get quick and reliable solutions to your questions from a community of experienced professionals on our platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To find the pair of points representing the solution set of the system of equations:
1. First, we have the equations:
[tex]\[ y = x^2 - 2x - 19 \][/tex]
[tex]\[ y + 4x = 5 \][/tex]
2. We substitute the expression for [tex]\(y\)[/tex] from the second equation into the first equation. From the second equation, solve for [tex]\(y\)[/tex]:
[tex]\[ y = 5 - 4x \][/tex]
3. Substitute [tex]\( y = 5 - 4x \)[/tex] into the first equation:
[tex]\[ 5 - 4x = x^2 - 2x - 19 \][/tex]
4. Rearrange the equation to form a standard quadratic equation:
[tex]\[ x^2 - 2x - 19 - 5 + 4x = 0 \][/tex]
[tex]\[ x^2 + 2x - 24 = 0 \][/tex]
5. Factorize or use the quadratic formula to solve for [tex]\(x\)[/tex]. The quadratic formula is given by:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Here, [tex]\( a = 1 \)[/tex], [tex]\( b = 2 \)[/tex], and [tex]\( c = -24 \)[/tex].
[tex]\[ x = \frac{-2 \pm \sqrt{2^2 - 4(1)(-24)}}{2(1)} \][/tex]
[tex]\[ x = \frac{-2 \pm \sqrt{4 + 96}}{2} \][/tex]
[tex]\[ x = \frac{-2 \pm \sqrt{100}}{2} \][/tex]
[tex]\[ x = \frac{-2 \pm 10}{2} \][/tex]
This gives us two solutions for [tex]\(x\)[/tex]:
[tex]\[ x = \frac{8}{2} = 4 \][/tex]
[tex]\[ x = \frac{-12}{2} = -6 \][/tex]
6. Substitute these [tex]\(x\)[/tex]-values back into the second equation to find the corresponding [tex]\(y\)[/tex]-values:
For [tex]\( x = 4 \)[/tex]:
[tex]\[ y = 5 - 4(4) = 5 - 16 = -11 \][/tex]
For [tex]\( x = -6 \)[/tex]:
[tex]\[ y = 5 - 4(-6) = 5 + 24 = 29 \][/tex]
The pair of points representing the solutions to the system of equations are [tex]\((-6, 29)\)[/tex] and [tex]\((4, -11)\)[/tex].
Therefore, the missing pair of points is:
[tex]\[ (4, -11) \][/tex]
1. First, we have the equations:
[tex]\[ y = x^2 - 2x - 19 \][/tex]
[tex]\[ y + 4x = 5 \][/tex]
2. We substitute the expression for [tex]\(y\)[/tex] from the second equation into the first equation. From the second equation, solve for [tex]\(y\)[/tex]:
[tex]\[ y = 5 - 4x \][/tex]
3. Substitute [tex]\( y = 5 - 4x \)[/tex] into the first equation:
[tex]\[ 5 - 4x = x^2 - 2x - 19 \][/tex]
4. Rearrange the equation to form a standard quadratic equation:
[tex]\[ x^2 - 2x - 19 - 5 + 4x = 0 \][/tex]
[tex]\[ x^2 + 2x - 24 = 0 \][/tex]
5. Factorize or use the quadratic formula to solve for [tex]\(x\)[/tex]. The quadratic formula is given by:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Here, [tex]\( a = 1 \)[/tex], [tex]\( b = 2 \)[/tex], and [tex]\( c = -24 \)[/tex].
[tex]\[ x = \frac{-2 \pm \sqrt{2^2 - 4(1)(-24)}}{2(1)} \][/tex]
[tex]\[ x = \frac{-2 \pm \sqrt{4 + 96}}{2} \][/tex]
[tex]\[ x = \frac{-2 \pm \sqrt{100}}{2} \][/tex]
[tex]\[ x = \frac{-2 \pm 10}{2} \][/tex]
This gives us two solutions for [tex]\(x\)[/tex]:
[tex]\[ x = \frac{8}{2} = 4 \][/tex]
[tex]\[ x = \frac{-12}{2} = -6 \][/tex]
6. Substitute these [tex]\(x\)[/tex]-values back into the second equation to find the corresponding [tex]\(y\)[/tex]-values:
For [tex]\( x = 4 \)[/tex]:
[tex]\[ y = 5 - 4(4) = 5 - 16 = -11 \][/tex]
For [tex]\( x = -6 \)[/tex]:
[tex]\[ y = 5 - 4(-6) = 5 + 24 = 29 \][/tex]
The pair of points representing the solutions to the system of equations are [tex]\((-6, 29)\)[/tex] and [tex]\((4, -11)\)[/tex].
Therefore, the missing pair of points is:
[tex]\[ (4, -11) \][/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.